การเลือกใช้วิธีอิมมูโนฟลูออเรสเซนต์หรือวิธีอิมมูโนฮีสโตเคมี เพื่อการวินิจฉัยเนื้อเยื่อทางพยาธิวิทยา - ปรานอม ภูชฎาภิรมย์ (2018)
Immunofluorescent and immunohistochemistry are pillars of modern diagnostic techniques, which are Antigen-Antibody complex basis. Both techniques are sensitive and highly specific to particular antigen. However, immunofluorescent differs from immunohistochemistry in many aspects. For example, tissue collection and preparation, chemical reactions, fluorescent microscope and/or confocal laser scanning microscope versus compound microscope. Furthermore, some sensitive tissues such as kidneys need to be collected and preparedly with different methods. The Antigen-Antibody complexes in kidney are destroyed by formalin solution, thus freshly kidneys are suggested. To summarize, pathologists who use Immunofluorescent and Immunohistochemistry for diagnosis should realize that the proper techniques of collecting and preparing specimen could lead to the accurate results.